Numerical study of polymer fluid flows in the channel of a screw extruder using one-and two-dimensional models - Subbotin, Evgeniy Vladimirovich; Trufanova, Nataliya Mikhailovna; Shcherbinin, Aleksey Grigorievich (Computational Continuum Mechanics, 2012)
This paper is devoted to numerical modeling of viscous fluid flows in the channels of screw pumps. The results of computational experiments obtained using different mathematical models are given. The analysis of the influence of the mathematical model dimension, curvature, channel geometry, rheological properties of the material on the calculation results is performed.The applicability of the models used in this study is verified.
Keywords: polymer flow; numerical modeling; pressure drop-flow rate characteristics